Congestion pricing vs. slot constraints to airport networks - Achim I. Czerny (Technische Universität Berlin, Fakultät Wirtschaft und Management, 2006)
Congestion has become a problem for many airports throughout the world. Two different policy options to control congestion are analyzed in this paper: slot constraints and congestion pricing. In particular, our model takes into account that the airline industry is characterized by significant demand uncertainty. Furthermore, due to the network character of the airline industry, the demand for airport capacities normally is complementary. We show that this favors the use of slot constraints compared to congestion pricing from a social point of view. In contrast, for monopolistic airports, prices as instruments constitute a dominant choice.
Keywords: D42; L93; 330; Slots; uncertainty; monopolistic airports; regulation; Flughafen; Bottleneck; Verkehrstarif; Netzzugang; Luftverkehrspolitik; Monopol; Wohlfahrtseffekt; Theorie